Cybervictimization among secondary students: social networking time, personality traits and parental education - Mónica Rodríguez-Enríquez; Miquel Bennasar-Veny; Alfonso Leiva; Maite Garaigordobil; Aina M. Yañez (BMC, 2019)
Abstract Background Cyberbullying among children and adolescents is a major public health concern. However, research has not yet definitively identified the risk factors associated with cybervictimization. The purpose of this study was to determine the association of cybervictimization with use of social networks, personality traits and parental education in secondary students. Methods The study population consisted of 765 secondary students (56.5% girls) from Majorca (Spain) who were aged 15.99 years (grade 4). The data were from the 16 secondary school centers that participated in the ITACA Project, a multi-center, cluster randomized controlled trial. Cybervictimization was measured by the Garaigordobil Cybervictimization Scale, and the Big Five Questionnaire for Children was used to assess personality traits. Results Results showed that 39.9% of the students were cybervictims. Univariate analysis indicated that more girls than boys were cybervictimized (43.1% vs 35.7%). Cybervictims spent more time in social networking sites than non-victims (6 h 30 min vs. 5 h 16 min) and had greater emotional instability (0.16 vs. -0.23) and extraversion (0.11 vs. -0.09) and were less conscientious (− 0.001 vs. 0.20). Multivariable analysis indicated that social networking time was not significantly associated with cybervictimization after controlling for personality traits, but the same personality traits remained significantly associated. Conclusions Our findings indicate that cyberbullying is a frequent and relevant problem in adolescents. Big Five personality traits are related with cybervictimization. Possible ways to design interventions include promoting social leisure activities, encourage responsible attitudes and provide stress coping tools.